Information Society and Teaching Computer Science At The Present Stage Organizing Process Significance - Mamajanov Raxmatilla Yakubjanovich (Euro Asian Journal Publishing, 2024)
The improvement of information technologies in the education system involves refining the content, organizational forms, methods, and means of teaching to enhance the practical skills of future specialists and workers in the rapidly changing information environment. The article discusses the relevance of organizing computer science education at the present stage of forming an information society and presents effective tools and methods for their implementation.
Keywords: Education; experience; information; society